Pengaruh Motivasi, Komunikasi, dan Stres Kerja Terhadap Kinerja Karyawan Alihdaya Laboratorium di PT. Bukit Asam Tbk. Unit Pelabuhan Tarahan - Ni Putu Widhia Rahayu; Rizka Rachmaniar (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research examines how motivation, communication, and work stress influence employee performance at PT Bukit Asam Tbk, Tarahan Port Unit. Data were collected from 30 employees using a questionnaire and analyzed with validity tests, normality tests, multiple linear regression, partial t tests, and an F test. All questionnaire items were valid. The normality test showed that the data met the normal distribution requirement with an Asymp. Sig. value of 0.200. The regression results indicated that motivation and communication improved employee performance. Higher stress levels reduced performance. The t test results supported these findings. Motivation had a significant effect on performance (t 2.300, Sig. 0.030). Communication also showed a significant effect (t 2.244, Sig. 0.034). Work stress had a significant negative effect (t −2.116, Sig. 0.044). The F test value of 34.780 confirmed that all variables together affected performance. The study suggests that PT Bukit Asam Tbk should strengthen motivation programs, improve communication practices, and manage work stress effectively to support better employee performance.